Mind the gap: comparing exploration effort with global biodiversity patterns and climate projections to determine ocean areas with greatest exploration needs - Brian R. C. Kennedy; Randi D. Rotjan (Frontiers in Marine Science, 2023)
The oceans contain 1,335 million km 3 of water covering 361.9 million km 2 of seafloor across 71% of the planet. In the past few decades, there has been substantial effort put into mapping and exploring the ocean fueled by the advent of new technologies that more easily enable deepwater access. However, we are still far from achieving our shared goals of a well characterized and documented ocean. In 2010, Webb et al. documented the paucity of deep-sea data in general, with a specific focus on the lack of pelagic records in the Ocean Biogeographic Information System OBIS, which is the largest of the ocean biodiversity archives. While significant exploration progress has been made, the rate of change in the ocean is outstripping the rate of characterization and research. Given the limited resources available, future work needs to be prioritized to focus on areas of greatest need. Here, we investigated several lines of inquiry to determine priority areas for future exploration. We accumulated the largest database of global deep submergence dive records ever compiled and used it, plus OBIS biodiversity records, to assess the level of exploration in different ocean regions. Then, we compared these measures of exploration effort with different biogeographic province schemas and estimates of climate change velocity projections to identify the largest remaining gaps in exploration and research sampling. Given that marine science has only explored between 5 and 20% of the ocean (depending on estimates) in the last hundred and fifty years, future exploration needs to be more targeted to attempt to keep pace with the rate and impact of environmental and biodiversity change in the ocean.

Low-Cost, Deep-Sea Imaging and Analysis Tools for Deep-Sea Exploration: A Collaborative Design Study - Katherine L. C. Bell; Jennifer Szlosek Chow; Alexis Hope; Maud C. Quinzin; Kat A. Cantner; Diva J. Amon; Jessica E. Cramp; Randi D. Rotjan; Lehua Kamalu; Asha de Vos; Sheena Talma; Salome Buglass; et al. (Frontiers in Marine Science, 2022)
A minuscule fraction of the deep sea has been scientifically explored and characterized due to several constraints, including expense, inefficiency, exclusion, and the resulting inequitable access to tools and resources around the world. To meet the demand for understanding the largest biosphere on our planet, we must accelerate the pace and broaden the scope of exploration by adding low-cost, scalable tools to the traditional suite of research assets. Exploration strategies should increasingly employ collaborative, inclusive, and innovative research methods to promote inclusion, accessibility, and equity to ocean discovery globally. Here, we present an important step toward this new paradigm: a collaborative design study on technical capacity needs for equitable deep-sea exploration. The study focuses on opportunities and challenges related to low-cost, scalable tools for deep-sea data collection and artificial intelligence-driven data analysis. It was conducted in partnership with twenty marine professionals worldwide, covering a broad representation of geography, demographics, and domain knowledge within the ocean space. The results of the study include a set of technical requirements for low-cost deep-sea imaging and sensing systems and automated image and data analysis systems. As a result of the study, a camera system called Maka Niu was prototyped and is being field-tested by thirteen interviewees and an online AI-driven video analysis platform is in development. We also identified six categories of open design and implementation questions highlighting participant concerns and potential trade-offs that have not yet been addressed within the scope of the current projects but are identified as important considerations for future work. Finally, we offer recommendations for collaborative design projects related to the deep sea and outline our future work in this space.

Historical Trends of Sperm Whale (Physeter macrocephalus) Distribution in the Phoenix Archipelago - Brian R. C. Kennedy; Lara Hakam; Jan Witting; Regen Milani; Sue Taei; Tim Smith; Erin Taylor; Tooreka Teemari; Randi D. Rotjan (Frontiers in Marine Science, 2021)
The Phoenix Archipelago in the Central Pacific is situated in what was once one of the most productive areas for capturing sperm whales ( Physeter macrocephalus ). These whales were the focal targets of American offshore whalers in the mid-19th century along the equator, an area known as the “on-the-line” whaling grounds. Now, as large-scale Marine Protected Areas (MPAs) have provided protection for marine mammals and their food sources, it is important to have a solid understanding of historical baselines so recovery distributions can be compared with pre-whaling distributions. The Phoenix Islands archipelago contains two large MPAs: the Phoenix Islands Protected Area (PIPA), established by Kiribati in 2008, and the Howland/Baker unit of the Pacific Remote Islands Marine National Monument (PRIMNM), established by the United States in 2009. Using historic whaling records from American whaling vessels operated through the wider Phoenix Archipelago region, we reconstructed information about the presence and distribution of P. microcephalus throughout the 1800s within and around PIPA and the Howland/Baker units of the PRIMNM. Historical data analyzed using ArcGIS showed that sperm whales were present year-round within the study area, which is consistent with 20th century records from the Ocean Biogeographic Information System (OBIS). A Getis Ord Gi ∗ hotspot analysis also revealed sighting hotspots within PIPA and near Howland and Baker, suggesting that these two areas may be of long-term ecological importance to sperm whales in the central Pacific. The New England whaling fleet ceased whaling effort in the central Pacific in the late 1800s, and publicly available records since that time are scarce. There has been no modern systematic whale survey ever conducted within the Phoenix Archipelago, though anecdotal accounts and sightings have been compiled over the years. These intermittent accounts suggest that though whale populations have not recovered to pre-whaling baselines, large-scale MPAs may play a role in helping to foster a resurgence of marine mammal populations. As the network of large-scale MPAs continue to grow as part of the commitment to ocean conservation set forth by UNESCO, IUCN, and the UN Decade for Ocean Science, historical baselines will be critical as a “yardstick” to measure population resurgence success for each MPA, and for populations overall.

Deep-Sea Debris in the Central and Western Pacific Ocean - Diva J. Amon; Brian R. C. Kennedy; Kasey Cantwell; Kelley Suhre; Deborah Glickson; Timothy M. Shank; Randi D. Rotjan (Frontiers in Marine Science, 2020)

Corrigendum: The Unknown and the Unexplored: Insights Into the Pacific Deep-Sea Following NOAA CAPSTONE Expeditions - Brian R. C. Kennedy; Kasey Cantwell; Mashkoor Malik; Christopher Kelley; Jeremy Potter; Kelley Elliott; Elizabeth Lobecker; Lindsay McKenna Gray; Derek Sowers; Michael P. White; Scott C. France; Steven Auscavitch; et al. (Frontiers in Marine Science, 2020)

Oceanographic Drivers of Deep-Sea Coral Species Distribution and Community Assembly on Seamounts, Islands, Atolls, and Reefs Within the Phoenix Islands Protected Area - Steven R. Auscavitch; Mary C. Deere; Abigail G. Keller; Randi D. Rotjan; Timothy M. Shank; Erik E. Cordes (Frontiers in Marine Science, 2020)

Correction to: Skeletal records of bleaching reveal different thermal thresholds of Pacific coral reef assemblages - Nathaniel R. Mollica; Anne L. Cohen; Alice E. Alpert; Hannah C. Barkley; Russell E. Brainard; Jessica E. Carilli; Thomas M. DeCarlo; Elizabeth J. Drenkard; Pat Lohmann; Sangeeta Mangubhai; Kathryn R. Pietro; Hanny E. Rivera; et al. (Coral Reefs, 2019)

The Unknown and the Unexplored: Insights Into the Pacific Deep-Sea Following NOAA CAPSTONE Expeditions - Brian R. C. Kennedy; Kasey Cantwell; Mashkoor Malik; Christopher Kelley; Jeremy Potter; Kelley Elliott; Elizabeth Lobecker; Lindsay McKenna Gray; Derek Sowers; Michael P. White; Scott C. France; Steven Auscavitch; et al. (Frontiers in Marine Science, 2019)

Skeletal records of bleaching reveal different thermal thresholds of Pacific coral reef assemblages - Nathaniel R. Mollica; Anne L. Cohen; Alice E. Alpert; Hannah C. Barkley; Russell E. Brainard; Jessica E. Carilli; Thomas M. DeCarlo; Elizabeth J. Drenkard; Pat Lohmann; Sangeeta Mangubhai; Kathryn R. Pietro; Hanny E. Rivera; et al. (Coral Reefs, 2019)

A simple temperature-based model predicts the upper latitudinal limit of the temperate coral Astrangia poculata - J. L. Dimond; A. H. Kerwin; R. Rotjan; K. Sharp; F. J. Stewart; D. J. Thornhill (Coral Reefs, 2013)

New records of corallivory in the Red Sea - M. L. Berumen; R. D. Rotjan (Coral Reefs, 2010)